2023
DOI: 10.2967/jnumed.122.264964
|View full text |Cite
|
Sign up to set email alerts
|

Prostate-Specific Membrane Antigen Expression on PET/CT in Patients with Metastatic Castration-Resistant Prostate Cancer: A Retrospective Observational Study

Abstract: Rationale: Monitoring therapy response in patients with metastatic castration-resistant prostate cancer ([m]CRPC) treated with novel hormonal therapies, taxanes and newly approved therapies is crucial for optimizing treatment. [ 68 Ga]Ga-prostate-specific membrane antigen (PSMA)-11 positron emission tomography/computed tomography (PSMA PET/CT) is a promising target for managing treatment in patients with prostate cancer. PSMA is overexpressed in patients with mCRPC; understanding how expression might change in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“… 18 In detail, while the analysis conducted by Esen et al. showed considerable concordance between 68 Ga-PSMA PET data and PSA response, 26 Calderoni and colleagues suggested that 68 Ga-PSMA PET could possibly represent a better prognostic factor than PSA in terms of PFS, 20 suggesting that this novel imaging technique may play a crucial role in treatment response evaluation in mCRPC.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“… 18 In detail, while the analysis conducted by Esen et al. showed considerable concordance between 68 Ga-PSMA PET data and PSA response, 26 Calderoni and colleagues suggested that 68 Ga-PSMA PET could possibly represent a better prognostic factor than PSA in terms of PFS, 20 suggesting that this novel imaging technique may play a crucial role in treatment response evaluation in mCRPC.…”
Section: Discussionmentioning
confidence: 98%
“…Nonetheless, our analysis adds to previous preliminary data in the literature supporting the use of 68 Ga-PSMA PET for the precocious assessment of therapy with ARTA. 18 , 20 , 26 , 27 However, even if carried out on a larger sample size, three of these above-mentioned studies were characterized by a retrospective design, 20 , 26 , 27 of which one enrolled both mHSPC and mCRPC patients, 26 and the other one was a systematic review of the literature. 18 In detail, while the analysis conducted by Esen et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past few years, the U.S. Food and Drug Administration (FDA) has approved three diagnostic imaging agents for positron emission tomography (PET) imaging: [ 68 Ga]­Ga-PSMA-11 (Ga68 gozetotide), [ 18 F]­DCFPyL (PYLARIFY, piflufolastat F18), and [ 18 F]­rhPSMA-7.3 (POSLUMA, flotufolostat F 18) (Figure ). PET imaging studies in conjunction with the PSMA-targeting agents are now routinely applied in nuclear medicine clinics to assist the diagnosis and monitoring therapy for patients with prostate cancer (Figure ). Additionally, radioligand therapy (RLT) based on PSMA targeting, using α- or β-emitting radionuclides (actinium-225 or lutetium-177), is a new area of drug development for the treatment of various tumors, including prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…PSMA-PET uses radiotracers specifically targeting the prostate-specific membrane antigen (PSMA), a surface protein highly overexpressed by most prostate cancer cells, allowing for highly sensitive and specific detection of prostate cancer manifestations. Recent studies indicate that PSMA-PET is not only highly sensitive in the detection of prostate cancer lesions but that change in PSMA uptake under therapy can serve as a marker for treatment response [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%